A national comparison of burnout and work‐life balance among internal medicine hospitalists and outpatient general internists. Issue 3 (16th January 2014) - Roberts, Daniel L.; Shanafelt, Tait D.; Dyrbye, Liselotte N.; West, Colin P.
<x xml:space="preserve">Abstract</x> BACKGROUND General internists suffer higher rates of burnout and lower satisfaction with work‐life balance than most specialties, but the impact of inpatient vs outpatient practice location is unclear. METHODS Physicians in the American Medical Association Physician Masterfile were previously surveyed about burnout, depression, suicidal ideation, quality of life, fatigue, work‐life balance, career plans, and health behaviors. We extracted and compared data for these variables for the 130 internal medicine hospitalists and 448 outpatient general internists who participated. Analyses were adjusted for age, sex, hours worked, and practice setting. RESULTS There were 52.3% of the hospitalists and 54.5% of the outpatient internists affected by burnout (P = 0.86). High scores on the emotional exhaustion subscale (43.8% vs 48.1%, P = 0.71) and on the depersonalization subscale (42.3% vs 32.7%, P = 0.17) were common but similar in frequency in the 2 groups. Hospitalists were more likely to score low on the personal accomplishment subscale (20.3% vs 9.6%, P = 0.04). There were no differences in symptoms of depression (40.3% for hospitalists vs 40.0% for outpatient internists, P = 0.73) or recent suicidality (9.2% vs 5.8%, P = 0.15). Rates of reported recent work‐home conflict were similar (48.4% vs 41.3%, P = 0.64), but hospitalists were more likely to agree that their work schedule leaves enough time for their personal life and family (50.0% vs 42.0%, P = 0.007). CONCLUSIONS Burnout was common among both hospitalists and outpatient general internists, although hospitalists were more satisfied with work‐life balance. A better understanding of the causes of distress and identification of solutions for all internists is needed. Journal of Hospital Medicine 2014;9:176–181. © 2014 Society of Hospital Medicine